Protective Effects of Costunolide Against D-Galactosamine and Lipopolysaccharide-Induced Acute Liver Injury in Mice - Mao, Jingxin; Yi, Man; Wang, Rui; Huang, Yuanshe; Chen, Min (Frontiers in Pharmacology, 2018)
Costunolide, a sesquiterpene isolated from Vladimiria souliei (Franch.) Ling, is known to exhibit anti-inflammatory, anti-viral, and anti-tumor activities. However, the effects of costunolide on liver injury are poorly understood. The current study aimed to investigate the hepatoprotective effects of costunolide against lipopolysaccharide (LPS) and D-galactosamine-induced acute liver injury (ALI) in mice. The results indicated that costunolide (40 mg/kg) could significantly improve the pathological changes of hepatic tissue, and reduced the LPS and D-galactosamine-induced increases of alanine aminotransferase (from 887.24 ± 21.72 to 121.67 ± 6.56 IU/L) and aspartate aminotransferase (from 891.01 ± 45.24 to 199.94 ± 11.53 IU/L) activities in serum. Further research indicated that costunolide significantly reduced malondialdehyde content (from 24.56 ± 1.39 to 9.17 ± 0.25 nmol/ml) and reactive oxygen species (from 203.34 ± 7.68 to 144.23 ± 7.12%), increased the activity of anti-oxidant enzymes superoxide dismutase (from 153.74 ± 10.33 to 262.27 ± 8.39 U/ml), catalase (from 6.12 ± 0.30 to 12.44 ± 0.57 U/ml), and total anti-oxidant capacity (from 0.64 ± 0.06 to 6.29 ± 0.11 U/ml) in hepatic tissues. Western blot results revealed that costunolide may trigger the anti-oxidative defense system by inhibiting kelch-like ECH-associated protein 1 and nuclear factor-related factor 2 (cytosol), increasing nuclear factor-related factor 2 (nucleus), heme oxygenase-1 and NAD (P) H quinone oxidoreductase 1 activity. Moreover, costunolide significantly decreased the protein expression of proinflammatory cytokines including interleukin 1β, interleukin 6, and tumor necrosis factor. Pretreatment with costunolide could reduce the expression of toll-like receptor 4, myeloid differentiation factor 88, p65 (Nucleus), phosphorylated IκB kinase α/β, inhibitor of nuclear factor kappa-B kinase, inhibitor kappa Bα and prevent the expression of phosphorylated inhibitor kappa B kinase which repressed translocation of p65 from cytoplasm to nucleus. In addition, pretreatment with costunolide also inhibited hepatocyte apoptosis by reducing the expression of B-cell lymphoma 2 associated X, cytochrome C, cysteinyl aspartate specific proteinase 3, cysteinyl aspartate specific proteinase 8 and cysteinyl aspartate specific proteinase 9, and by increasing B-cell lymphoma 2. From the above analysis, the protective effects of costunolide against LPS and D-galactosamine-induced ALI in mice may be attributed to its anti-oxidative activity in nuclear factor-related factor 2 signaling pathways, anti-inflammatory suppression in nuclear factor-kappa B signaling pathways, and inhibition of hepatocyte apoptosis. Thus, costunolide may be a potential therapeutic agent in attenuating LPS and D-galactosamine -induced ALI in the future.